Reading and Re-Reading Scripture at Qumran (2 vol. set) - Bernstein, Moshe J. (Leiden : BRILL, 2013)
In Reading and Re-reading Scripture at Qumran, Moshe J. Bernstein gathers over three decades worth of his essays on biblical interpretation in the Dead Sea Scrolls. They address the Genesis Apocryphon and 4Q252, as well various legal texts and pesharim.
Chapter Eighteen Pseudepigraphy in the Qumran Scrolls: Categories and FunctionsChapter Nineteen The Interpretation of Biblical Law in the Dead Sea Scrolls: Forms and Methods (with Shlomo A. Koyfman); Chapter Twenty What Has Happened to the Laws? The Treatment of Legal Material in 4QReworked Pentateuch; Chapter Twenty-One The Re-Presentation of "Biblical" Legal Material at Qumran: Three Cases from 4Q159 (4QOrdinances); Chapter Twenty-Two 4Q159: Nomenclature, Text, Exegesis, Genre; Chapter Twenty-Three 4Q159 Fragment 5 and the "Desert Theology" of the Qumran Sect.
Chapter Twenty-Nine "Walking in the Festivals of the Gentiles:" 4QpHosea 2:15-17 and Jubilees 6:34-38.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Dead Sea scrolls; Bible. -- Criticism, interpretation, etc., Jewish -- History -- To 1500.; RELIGION / Biblical Criticism & Interpretation / Old Testament; Electronic books